2011
DOI: 10.1158/0008-5472.can-10-2314
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression and Androgen Regulation of the Tumor Suppressor Gene INPP4B in Prostate Cancer

Abstract: Patients with metastatic prostate cancer who undergo androgen-ablation therapy invariably relapse and develop incurable castration-resistant disease. Activation of the prosurvival Akt pathway accompanies androgen ablation. We discovered that the androgen receptor induces the expression of the tumor suppressor inositol polyphosphate 4-phosphatase type II (INPP4B) but not PTEN in prostate cancer cells. Optimal induction of INPP4B by an androgen receptor required the expression of the transcriptional coactivator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(191 citation statements)
references
References 55 publications
11
168
1
Order By: Relevance
“…70 Recently, INPP4B, a 4′ phosphoinositide phosphatase that specifically dephosphorylates PI-3,4-P2, and by this further inhibits Akt, has been described as a tumor suppressor in breast and prostate cancers. [71][72][73] It would be worth investigating whether SHIP-2 or INPP4B inactivation coexists with PTEN loss in a subset of these tumors, leading to higher Akt activation and thus to another convergent mechanism of PI3K-Akt activation.…”
Section: Pten Loss and Intrapathway Additive Activationmentioning
confidence: 99%
“…70 Recently, INPP4B, a 4′ phosphoinositide phosphatase that specifically dephosphorylates PI-3,4-P2, and by this further inhibits Akt, has been described as a tumor suppressor in breast and prostate cancers. [71][72][73] It would be worth investigating whether SHIP-2 or INPP4B inactivation coexists with PTEN loss in a subset of these tumors, leading to higher Akt activation and thus to another convergent mechanism of PI3K-Akt activation.…”
Section: Pten Loss and Intrapathway Additive Activationmentioning
confidence: 99%
“…For example, in estrogen receptor (ER) þ breast cancers, activating mutations in the catalytic subunit of PI3Ka are common, whereas mutations in AKT1 and PTEN occur at lower frequency (3). In prostate cancer, loss of phosphatases including PTEN and INPP4B are common (4)(5)(6). In contrast to the RAF-MEK-ERK pathway, signaling through the PI3K/AKT/mTOR signaling network is noncanonical; the presence of mutations in multiple signaling components in tumor types such as endometrial (7) and bladder (8) supports this concept.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is reported that INPP4B is highly expressed in prostate intermediate cells 7 but decreased in PCa tissues. 6 Cumulative evidences have demonstrated that loss of INPP4B expression correlates with disease recurrence and poor clinical outcome for PCa patients. 7 Moreover, INPP4B was proved to be an androgen responsive gene, 6 and overexpression of INPP4B contributes to an antitumor effect in therapy for CRPC.…”
Section: Introductionmentioning
confidence: 99%